The Implementation of Text-Based Approach within the Competency-Based Curriculum in Senior High School - Bila, Yashara Salsa; Oktarina, Elsa; Putri, Rizka Zhafira; Hasibuan, Kalayo (Lembaga Riset dan Inovasi Almatani, 2024)
This article discusses the integration of the text-based approach within the curriculum 2004, The Competency-Based Curriculum (CBC), also known as the CBC, in senior high schools. The text-based approach, which emphasizes the use of authentic texts and The Competency-Based Curriculum (CBC) operates through a systematic cycle that includes building knowledge, modeling, joint construction, and independent construction, all of which are essential for language learning and skill development. It promotes genuine language learning, critical thinking, learner autonomy, collaboration, and the integration of content knowledge, aligning with the curriculum's goal of fostering competent communicators. Effective strategies under this approach include activating prior knowledge, guided text exploration, collaborative construction, scaffolded writing, peer and self-assessment, multimedia integration, text-based instruction, and project-based learning. Research highlights improvements in students' reading comprehension, writing proficiency, listening and speaking abilities, language awareness, and critical thinking. Additionally, it enhances learner autonomy, motivation, engagement, and content knowledge. The alignment between the text-based approach and the Competency-Based Curriculum (CBC) framework not only enhances language proficiency but also supports the overall goal of producing well-rounded, competent individuals capable of effective communication and critical thinking. This ensures that students are well-prepared for future academic and professional challenges.